Circulating Serum Exosomal Long Non-Coding RNAs FOXD2-AS1, NRIR, and XLOC_009459 as Diagnostic Biomarkers for Colorectal Cancer - Yu, Miao; Song, Xing-guo; Zhao, Ya-jing; Dong, Xiao-han; Niu, Li-min; Zhang, Zhi-jun; Shang, Xiao-ling; Tang, You-yong; Song, Xian-rang; Xie, Li (Frontiers in Oncology, 2021)
Background: Long non-coding RNAs (lncRNAs) had shown the ability to modulate tumor growth and metastasis and been proposed as diagnostic and prognostic biomarkers for cancer detection. The aim of this study was to identify a few circulating serum exosomal lncRNAs for the diagnosis of colorectal cancer (CRC). Materials and Methods: Exosomes were isolated from the serum of all participants by ultracentrifugation, after which they were verified by transmission electron microscope (TEM), qNano and immunoblotting. The exosomes isolated from 4 CRC patients and 2 healthy donors were subjected to RNA isolation and lncRNA sequencing. QRT-PCR was performed to screen and evaluate the expressions of candidate exosomal lncRNAs in 203 primary CRC patients and 201 healthy donors. The receiver operating characteristic curve (ROC) was used to assess the diagnostic efficiency of serum exosomal lncRNAs. Results: Sixteen candidate lncRNAs were screened according to the results of lncRNA sequencing and gene expression. Only serum exosomal FOXD2-AS1 and NRIR and XLOC_009459 (TCONS_00020073) levels were signiﬁcantly upregulated in 203 CRC patients and 80 early- stage CRC patients compared to 201 healthy donors and 20 benign diseases, the area under the curve (AUC) was 0.736, 0.758. In addition, the expression levels of exosomal FOXD2-AS1 and NRIR and XLOC_009459 were signiﬁcantly decreased postoperatively as compared to the baseline level determined before surgery. Conclusions: Exosomal lncRNAs FOXD2-AS1, NRIR and XLOC_009459 may serve as potential non-invasive, sensitive and specific biomarkers for diagnosis of CRC patients and early-stage of CRC patients.